Mixed weak-type inequalities in Euclidean spaces and in spaces of the homogeneous type - Ibañez-Firnkorn, Gonzalo; Rivera Ríos, Israel P. (Wiley, 2023)
In this paper, we provide mixed weak-type inequalities generalizing previous results in an earlier work by Caldarelli and the second author and also in the spirit of earlier results by Lorente et al. One of the main novelties is that, besides obtaining estimates in the Euclidean setting, results are provided as well in spaces of the homogeneous type, being the first mixed weak-type estimates that we are aware of in that setting.
Keywords: Análisis matemático; Matemáticas aplicadas; commutators; Hörmander operators; mixed weighted inequalities